Effects of pore widening vs oxygenation on capacitance of activated carbon in aqueous sodium sulfate electrolyte - Zhang, Lixing; Chi, Yuqin; Li, Zhen; Sun, Xiaolei; Gu, Huazhi; Zhang, Haijun; Chen, Yao; Chen, George Zheng (Institute of Physics Publishing, 2020)
The commercial activated carbon has a relatively low specific capacitance in the Na2SO4 electrolyte, which hinder the development of asymmetrical supercapacitors with high voltage. Re-activation and oxidative etching methods were applied to change the pore structure of activated carbon, respectively, to study the capacitive behavior of carbon in the Na2SO4 electrolyte. The pore distributions combining with capacitive properties deduce that 0.85 nm is the threshold diameter of the ion-accessible micropores for hydrated Na+ and SO42−. The specific capacitances of both the carbon materials by re-activation and oxidative etching methods are increased by 40 %, in comparison with the commercial activated carbon. The enhanced capacitive performances of the carbon materials were mainly attributed to the increased ion-accessible specific surface area and pseudocapacitance, respectively. The oxidative etching is a more facile and economical method for practice application. Combining with MnO2 as the positive electrode, the asymmetrical supercapacitor with a high voltage of 1.8 V exhibits a maximum specific cell capacitance of 50 F g–1 and specific energy of 22.5 Wh kg–1.